PENGARUH FAKTOR FUNDAMENTAL PERUSAHAAN PADA HARGA SAHAM: GOOD CORPORATE GOVERNANCE SEBAGAI PEMODERASI - sari, Tri Yunita; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine the influence of the firm fundamental factors on stock prices and the influenceof GCG in moderating the influence of the firm fundamental factors on stock prices. The results of the researchshow that: (a) ROA gives positive influence to the stock prices because ROA has increased the interest of investorsin wanting a large rate of return so it gives an impact to the enhancement of stock prices; (b) EPS gives positiveinfluence to the stock prices because EPS shows the company can generate high earnings per share which willincrease stock prices; (c) DER give positive influence to stock prices because high DER considered as the great ofcorporate responsibility to creditor; (d) GCG does not moderate the influence of ROA to stock prices becauseinvestors do not use information about GCG in monitoring profitability of the company to the stock prices; (e)GCG does not moderate the influence of EPS to stock prices because investors in the market do not see EPS throughGCG; (f) GCG positive moderates the influence of DER to stock prices because GCG can improve management ofthe company in ensuring that the loan funds from the creditors has been maximally utilized.Keywords: Return On Asset, Earning Per Share, Debt to Equity Ratio, Good Corporate Governance, share price.